A Conceptual Perspective of Internal Audit Effectiveness to Prevent Fraud - Miryam Pingkan Lonto (Budapest International Research and Critics University, 2022)
This study aims to synthesize relevant theoretical and empirical literature to develop a conceptual framework and propositions about the antecedents of the effectiveness of internal audits for fraud prevention. This study uses a literature review approach and uses institutional theory, organizational support theory, and quality theory to develop a conceptual framework and produce propositions that are theoretically justified and supported by previous research. Conceptual frameworks and propositions are provided on the antecedents of internal audit effectiveness and their possible relationship to audit quality and management support. This study combines the three theories to provide additional insight to identify the antecedents and effectiveness of internal auditing and generate a conceptual framework that did not exist before.